A Recipe for a Good and Stunning Presentation - Luita Yusniawati Dratistiana (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2018)
In modern world, knowledge keeps changing and challenges people to be more knowledgeable. One of them is a knowledge of making a presentation. The technique to deliver the presentation is upgraded during centuries. The challenge is bigger, since we are as a part of global world connected by super highway internet connection following more online classes, online seminars and the same other occasions. Attending those classes, we need to participate in delivering presentation which means we have to compete with other people from other side of world. Where to be accepted in such events, upgrading the presentation techniques is a must. Some theories to know the main points to deliver the presentation are the physical message which convey three parts: having a good stance in front of audience, gesture to boost confdence, facial expression and the voice inﬂection. In other hands, adding visual is also important to give special effect and to avoid boring situation. The last component to have an outstanding presentation is the story message. It is how to form the written language in a precise purpose